A dynamic response analysis of adhesive - Bonded single lap joints used in military aircrafts made of glass fiber composite material undercyclic impact loading. (October 2020) - Bautista, A.; Casas-Rodriguez, J.P.; Silva, M.; Porras, A.
Abstract: The Colombian aeronautical industry has stimulated research into the mechanical behaviours of materials under the different loading conditions that aircrafts are generally exposed during their operation. Calima T-90, the first military aircraft that was built in Colombia, is used for the primary flights training of Colombian Air Force pilots, and is thus often exposed to adverse operating situations, such as hard landings, which cause impact loads and can subsequently produce impact fatigue. The Calima T-90's structure is mainly comprised of composites materials, generating assemblies and subassemblies of different components of it. The main method of bonding these components is by using adhesive joints with different thicknesses. This study aimed to characterise these adhesive joints as they were placed under typical loads. For this purpose, an evaluation of the effects of adhesive thickness on the mechanical performances of such joints was accomplished and conducted using quasi-static loading conditions and impact fatigue, employing single lap-joint (SLJ) specimens. Cyclic impacts were induced using a drop weight impact testing machine, in order to obtain the characteristic impact-fatigue life diagrams. The evolution of dynamic parameters was then analysed such as residual strength, impact contact time and stiffness degradation; this was done for all the adhesive thicknesses tested. A modified phenomenological prediction model for strength degradation and a cycle to failure prediction model in terms of the adhesive thickness of the joint, mass and the impact strain rate were proposed. It was found that the impact fatigue life of the joints decreased as adhesive thicknesses increased under the same linear momentum, however, this did not occur when the specimens were subjected to similar impact energy values. Subsequently, an analysis of the fracture surfaces of the specimens was conducted that, considered the mechanical interactions between the substrate and the adhesive, fiber tearing and debonding from the composite matrix was found as well as delamination, resulting in a beneficial adhesion mechanism.